Human performance in transportation a comparative study of human performance models - Jalil, Azlis Sani; Md Dawal, Siti Zawiah; Mohmad Zakwan, Norhayati (International Journal of Engineering and Technology (IJET), 2012)
Human performance model (HPM) is an attempt to integrate and study the factors, and aspects influence the performance of a human during performing a job. Unfortunately, human factors and performance were left behind and be considered as independent factors with very fewer contributions to the system performance. The understanding of human performance will enable the analysis of potentially conflicting task demands in organized and structured ways as the earliest stages in a design. This paper is to address the importance of human performance to be considered in the transportation industry. Three keys human performance models were reviewed and presented for better understanding and to compare various factors influences the performance of a human.